PENGELOLAAN KEUANGAN DESA PADA DESA-DESA DI KABUPATEN KAMPAR - Daniatul Izzah; Taufeni Taufik; Vera Oktari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to determine the effect of community participation,transparency, accountability, quality of human resources,utilization of information technology and the implementation ofinternal control system on village financial management. Thisresearch was conducted in the village of Kampar Regency. Thepopulation in this study were village officials who worked at thevillage office in Kampar District, amounting to 242 villages. Thisstudy used purposive sampling. The number of samples in this studywere 150 respondents, from each village 5 respondents would betaken with the criteria of the Village Head, Village Secretary, Headof Finance, Section Chief and BPD. The test was carried out usingSPSS 25.0 for Windows and Microsoft Excel 2010. The analysistechnique in this study uses multiple regression analysis. Theresults of this study indicate that: (1) Community participationinfluences the effectiveness of village financial management;(2)Transparency influences the effectiveness of village financialmanagement; (3) Accountability influences the effectiveness ofvillage financial management; (4) The quality of human resourcesinfluences the effectiveness of village financial management; (5)The use of information technology influences the effectiveness ofvillage financial management; (6) The application of an internalcontrol system influences the effectiveness of village financialmanagement.